2020
DOI: 10.21203/rs.3.rs-41583/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of Oral Health Promotion Program for Persons with Severe Mental Illness: A Cluster Randomized Controlled Study

Abstract: Objective: To evaluate the effectiveness of a composite oral health promotion program designed to reduce dental plaque among persons with severe mental illness in a psychiatric institution. Methods: A cluster randomized controlled study was carried out in chronic psychiatric wards of a general hospital in central Taiwan. Sixty-eight eligible male individuals admitted to 2 wards were randomly assigned to an experimental and a control group. Participants in the experimental group underwent an oral health promoti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The findings in this study indicate the importance of using educational and behavioural interventions to improve oral health knowledge and motivation in patients diagnosed with a psychotic disorder (first‐episode). Literature showed effective interventions regarding oral health in patients diagnosed with a psychotic disorder (Almomani et al, 2006, 2009; Kuo et al, 2020; de Mey et al, 2016), however the stage a psychotic disorder was in (McGorry et al, 2007) and the effect thereof on OHRQoL were not identified. There is a need for studies exploring what kind of treatment can improve OHRQoL in young adults in general, and patients diagnosed with a psychotic disorder (first‐episode) especially.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings in this study indicate the importance of using educational and behavioural interventions to improve oral health knowledge and motivation in patients diagnosed with a psychotic disorder (first‐episode). Literature showed effective interventions regarding oral health in patients diagnosed with a psychotic disorder (Almomani et al, 2006, 2009; Kuo et al, 2020; de Mey et al, 2016), however the stage a psychotic disorder was in (McGorry et al, 2007) and the effect thereof on OHRQoL were not identified. There is a need for studies exploring what kind of treatment can improve OHRQoL in young adults in general, and patients diagnosed with a psychotic disorder (first‐episode) especially.…”
Section: Discussionmentioning
confidence: 99%
“…At this moment, no oral health interventions are available. However, oral health education, the use of a mechanical toothbrush, reminder systems and brief motivational interviewing sessions in patients diagnosed with SMI or psychotic disorders showed to be effective (Almomani et al, 2006, 2009; Kuo et al, 2020; de Mey et al, 2016). In all samples, oral health knowledge and oral health status (Quigley Hein plaque index) improved significantly.…”
Section: Discussionmentioning
confidence: 99%

Promoção de saúde bucal às pessoas com transtorno mental

Alves de Araújo Alcântara,
Jatobá Ramirez,
Cristina Ribeiro
et al. 2023
CadUniFOA